Th2A cells: The pathogenic players in allergic diseases - Huang, Ziyu; Chu, Ming; Chen, Xi; Wang, Ziyuan; Jiang, Lin; Ma, Yinchao; Wang, Yuedan (Frontiers in Immunology, 2022)
Proallergic type 2 helper T (Th2A) cells are a subset of memory Th2 cells confined to atopic individuals that include all the allergen-specific Th2 cells. Recently, many studies have shown that Th2A cells characterized by CD3+ CD4+ HPGDS+ CRTH2+ CD161high ST2high CD49dhigh CD27low play a crucial role in allergic diseases such as atopic dermatitis (AD), food allergy (FA), allergic rhinitis (AR), asthma, and eosinophilic esophagitis (EoE). In this review, we summarized the discovery, biomarkers, and biological properties of Th2A cells to gain new insights into the pathogenesis of allergic diseases.